Richard Dawkins : how a scientist changed the way we think : reflections by scientists, writers, and philosophers - Grafen, Alan.; Ridley, Mark. (Oxford ; New York : Oxford University Press, 2006)
This sparkling collection explores the impact of Richard Dawkins as scientist, rationalist, and one of the most important thinkers alive today. Leading figures from science, philosophy, literature, and the media reflect on the breadth and range of Dawkins' contributions to science and public debate, from evolutionary theory and artificial life, to rationalism and ethics. - ;This sparkling collection explores the impact of Richard Dawkins as scientist, rationalist, and one of the most important thinkers alive today. Specially commissioned pieces by leading figures in science, philosophy, litera.
List of Contributors; Preface; BIOLOGY; THE SELFISH GENE; LOGIC; ANTIPHONAL VOICES; HUMANS; CONTROVERSY; WRITING; Index.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Dawkins, Richard, -- 1941- -- Influence; Dawkins, Richard, -- 1941-; Behavior genetics; Evolution (Biology); Genetics, Behavioral; Evolution; Biological Evolution; Biology -- General; Biology; Health & Biological Sciences; Génétique du comportement; Évolution (Biologie); evolution; SCIENCE -- Life Sciences -- Zoology -- General; Evolution (Biology); Behavior genetics; Influence (Literary, artistic, etc.); Electronic books; Essay; essays; Essays; Essays; Essais